Public Health Emergencies: What Counts? - Gostin, Lawrence O. (The Hastings Center report, 2014)
Although Jonathan Herington, Angus Dawson, and Heather Draper offer valuable insights on how to conceptualize health hazards and understand their effects on populations, I resist the label “public health emergency” for obesity, and here is why. It is important—politically and pragmatically—to be judicious with words that have legal and real-world consequences. Once a concept is stretched to encompass a broad swath of events, it loses its power. The broader the application of the term “public health emergency,” the more it loses the core idea of an emergent event. Thus, framing a long-simmering health hazard such as obesity as an emergency would mute the voices of public health authorities seeking a surge response to a truly emergent event, such as a rapidly spreading novel disease or a natural or man-made disaster.